How consumers decide to buy during the pandemic Covid-19? - Nordin, Muhammad Iqbal; Hasim, Muhammad Asyraf; Harun, Amran (Penerbit UTHM, 2022)
A pandemic is a deadly disease that threatens society by spreading complex diseases and eventually spreads to other communities and areas. History shows that the world was once attacked by the flu pandemic, also known as the Spanish Flu, in 1918. The Spanish Flu 1918 has killed hundreds of millions of people over two years until the vaccine was found. Now, the world is shocked by a new pandemic called Covid-19. This pandemic is believed to have started in Wuhan, China, in December 2019 and has spread worldwide until today. Although the vaccines have been found and millions are already vaccinated, most countries are still closing their borders and enforcing lockdowns to combat Covid-19 infections from spreading wide. Covid-19 has crippled most companies' economic activities, especially small and medium enterprises (SMEs), and has significantly impacted consumer decision-making. Covid-19 has radically changed the context in which we make purchasing decisions, disrupting many deeply-rooted habits and preferences (Mledonova 2020).